Sublethal effects of spinosad and emamectin benzoate on larval development and reproductive activities of the cabbage moth, Mamestra brassicae L. (Lepidoptera: Noctuidae). (December 2016) - Moustafa, Moataz A.M.; Kákai, Ágnes; Awad, Mona; Fónagy, Adrien
Abstract: Lepidopteran insect pest management has relied heavily on synthetic chemical pesticides, but their efficiency is declining as a result of emerging insecticide resistance. Recently biopesticides have become the most promising products employed in pest management strategies. We investigated the sublethal effects of two bioinsecticides, spinosad and emamectin benzoate, on larval and pupal development, and reproductive activity including calling behaviour, pheromone production, fecundity and fertility of the cabbage moth, Mamestra brassicae . To assess sublethal effects, second instar larvae were fed with 0.005, 0.05, or 0.5 μg a.i. spinosad/g diet or 0.00005, 0.0005, or 0.005 μg a.i. emamectin benzoate/g diet. Both bioinsecticides significantly increased larval and pupal development time and negatively affected reproductive activity of M. brassicae . The calling activity of females decreased very significantly in the highest sublethal concentration of spinosad and in all treatments by emamectin benzoate. The results suggest that, both spinosad and emamectin benzoate are promising alternatives to conventional insecticides for the control of M. brassicae if successfully introduced into Integrated Pest Management (IPM) programs. Highlights: Sublethal effects of spinosad and emamectin benzoate mixed into diet were studied separately. Both bioinsecticides exerted significant negative effects on larval and pupal development. The calling activity of females treated in the 2nd larval instar decreased significantly. Spinosad and emamectin benzoate are potentially suitable for M. brassicae control.